Grain Size Effect on the Mechanical Behavior of Cohesionless Coarse-Grained Soils with the Discrete Element Method - Renjie Wen; Cai Tan; Yong Wu; Chen Wang (Advances in Civil Engineering)
Biaxial compression tests with the same specimen size and different maximum grain sizes were simulated for coarse-grained soils using the discrete element method to study the influence of grain size on the mechanical properties and force chain. The maximum grain sizes were 40, 20, 10, and 5 mm, respectively. The grading with self-similar fractal structure in mass is designed to ensure the same pore structure for soils. The shear strength increased with the increase in maximum grain size. Evident increase in shear strength and significant size effect were observed when the ratio of the specimen diameter to maximum grain size was less than five. The shear dilation of coarse-grained soils increases with the increase in maximum grain size. The contact force distribution was uniform when maximum grain size was small but tends to be uneven with the increase in maximum grain size, thereby causing the increase in shear strength by stable strong force chains. This finding demonstrates size effect on the mechanical properties and force chain of cohesionless coarse-grained soils under the biaxial compression condition.